Algorithms for the determination of unacceptable HLA antigen mismatches in kidney transplant recipients. Issue 2 (30th May 2013) - Süsal, C.; Roelen, D. L.; Fischer, G.; Campos, E. F.; Gerbase‐DeLima, M.; Hönger, G.; Schaub, S.; Lachmann, N.; Martorell, J.; Claas, F.
Abstract: One of the major tasks of human leukocyte antigen (HLA) laboratories is the pretransplant determination of unacceptable HLA antigen mismatches (UAM) in organ transplant recipients. HLA antigen specificities are determined against which the patient has circulating alloantibodies that are expected to harm the transplanted organ. Using the information on UAM, negative crossmatch (XM) prediction or 'virtual XM' is possible when a potential donor's complete HLA typing is available. Before the introduction of solid‐phase antibody detection assays, UAM were determined using the complement‐dependent cytotoxicity methodology. After the introduction of the single antigen bead technique, however, various UAM determination algorithms have emerged. In this report, six different laboratories worldwide present how they determine UAM in their collective of kidney transplant recipients in the pretransplant phase and proceed thereafter to transplantation.